Insect Pests Associated with Kikar and Shisham in Punjab - Sharma, Ajay; Verma, T. D.; Kaushal, P.; Kant, Chander (Indian Forester, 2003)
Kikar (Acacia nilotica Willd.) and Shisham (Dalbergia sissoo Roxb.) are integral part of agro-ecosystem in the plains of North-West India. In the recent past large scale mortality of these trees was observed in this area and other parts adjoining the North-West and North-East Himalayas. So as to investigate the different mortality factors of these trees in the State of Punjab some of the areas with large scale of mortality of these trees were surveyed during the year 2001 determining the insect-pest association. It was found that grubs of Coleopteran beetles were most predominant in dead and drying trees in most of the areas. However in certain case termites and bark eating caterpillars were also found associated with Kikar and Shisham trees. A detailed account of insect-pests associated with Kikar and Shisham trees and survey report in particular have been discussed in the text.